Autonomous fluorescence regulation in responsive polymer systems driven by a chemical oscillating reaction. Issue 19 (22nd April 2016) - Xu, Guohe; Zhou, Hongwei; Li, Jie; Yin, Lv; Zheng, Zhaohui; Ding, Xiaobin
Abstract : A new autonomous luminescence-regulated mechanism in responsive polymer systems based on autonomous structure change driven by a chemical oscillating reaction. Abstract : By utilizing a chemical oscillating reaction as a periodical driving source, the fluorescence in a responsive polymer system is autonomously regulated based on the reversible formation of dynamic covalent bonds.